perbandingan kadar HDL dan LDL akseptor Depo Medroksi Progesteron Asetat dengan IUD - Suci Syahril; Meldafia Idaman; Dewi Fransisca (HEALTH CARE : JURNAL KESEHATAN, 2018)
The use of contraceptive depot medroxyprogesterone acetate (DMPA) increasing lately, but some studies suggest has the side effects of weight gain and contraceptives that have side effect in lipid metabolism. Therefore, about 35% of acceptors of DMPA in the first year to stop the use of DMPA. The objective of this study was to determine the differences of lipid profile between acceptors DMPA with acceptors IUD. This was a obcervational study with cross sectional study. The study wasdone at health center Lubuk Buaya in Padang and at laboratory of Biochemistry Departement in Medical Faculty of Andalas University from Januari until September 2016. The subjects were consisted of two groups, each group had 26 subjects. The examination for LDL and HDL used an enzymatic colorimetric method CHOD-PAP. Data was analyzed using analysis of t-test with p < 0.05 was considered to be significantly different. HDL levels average in Depo Medroxyprogesterone Acetate was 87,54±14,28 mg/dl and IUD was 75,90±8,67 mg/dl with p < 0.05 (significantly difference). Levels of LDL means there is no significantly difference between DMPA and IUD acceptors (p> 0.05). This research concluded that there isa significant difference on average levels of HDL in the Depo Medroxyprogesterone Acetate and IUD but levels of LDL there is no significantly difference. The clinically lipid profile in the two groups is in normal range.